Inspiracje empirystyczne w filozofii matematyki. Część II - Wójtowicz, Krzysztof (Filozofia Nauki, 2015)
The article is devoted to the problem of mathematical empiricism: what could the phrase "to be a mathematical empiricist" mean? There are many interpretations of this position in philosophy of mathematics. The essay discusses relevant views of Quine and Putnam. Some detailed questions concerning e.g. the applicability of mathematics, the status of mathematical proof, the status of mathematical axioms are examined from the point of view of these philosophies.